Modeling the non-reversible series-resonant converter operating in zero voltage switching mode - Patrick Kuo- Peng; Yvon Chéron (Eletrônica de Potência)
This paper presents a steady state modeling of the non-reversible series-converter operating in Zero Voltage Switching (ZVS) mode. This modeling is based on the representation in the state plane of the converter steady state operation. This method enables a full characterization of the converter. The studied structure is composed of a full bridge inverter and a full bridge rectifier. It can be equipped with snubbers. The modeling method presented can also be applied to the variants of the basic one. Moreover, the analytical work is based on normalized quantities which lead to the derivation of dimensionless equations that characterize a structure instead of a particular circuit. The results of these analytical studies are integrated into a software which constitutes a powerful tool to design the converter.